first, set everything equal to zero.
n^2 - 10n + 21 = 0
now, since (n-a)(n-b) = n^2 - (a+b)n + ab, we are looking for two numbers a and b, which multiply to 21 and add to 10.
Now, the only factor of 21 are 7 and 3. Luckily, they add to 10, so we have
(n-7)(n-3) = n^2 - 10n + 21
Now, back to step 1. Why set everything to zero? We now have
(n-7)(n-3) = 0
the only way two numbers can multiply to zero is if one or the other of them is zero. So, we have either
n-7 = 0 ==> n=7
n-3 = 0 ==> n=3
Those are the solutions to
(n-7)(n-3) = 0, which is just a rewriting of the original equation.
algebra II - I'm quite clueless as to how to solve this. I know the quadratic ...
8th Grade Algebra - You know how to solve quadratic equations using algebra, ...
Algebra - Explain how to solve a quadratic equation using the quadratic formula.
algebra - Solve this quadratic equation using the quadratic formula. x^2 + 8x - ...
algebra - which quadratic formula would be used to solve the following quadratic...
pre calc - use the quadratic formula to solve for x. x^2+2x+5-0
math,algebra,help - Is this right: Solve: x^2+16x+60=0 this is what i did: i ...
Pre Algebra - Please help me with some problems. Thank you! Solve the equation ...
Pre-Calculus - How do you solve this quadratic function? f(x) = −x2 + 10x
College Algebra - Solve the following equation in the complex number system x^4+...